EFEKTIVITAS MEDIASI DALAM PENYELESAIAN PERKARA PERCERAIAN DI PENGADILAN AGAMA JAWA TENGAH - Muhammad Saifullah (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2015)
Mediation as one of Alternative Dispute Resolution (ADR) is seen as a way dispute resolution humane and just. Humanist because the mechanism decision-making (the peace agreement) become the authority of the parties dispute and maintain good relations. Fair because each party negotiate to option a problem solution from his problem and outputs a win-win solution. Therefore, dispute resolution with litigation is becoming obsolete and people turn to mediation. Through the Supreme Court Regulation (Perma) No. 1 In 2008, mediation has been integrated into the proceedings in the court system. Every civil matters must completed first by way of mediation. Each judge's decision not by way of mediation first, the decision shall be considered null and void. This paper discusses the effectiveness of mediation in the settlement of divorce cases in the Religious Court Central Java, because of a divorce case is a matter of the highest ranks in the Religious Court. The focus of the study is the implementation of divorce mediation cases, mediation success standard divorce cases and the litigants public response to the peace efforts through mediation procedures